GAMMA-BACKGROUND RADIATION CONTROL SYSTEMS AS A FACTOR OF BULGARIA'S NATIONAL SECURITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The sources of ionizing radiation and nuclear facilities on the territory of Bulgaria may cause a change in the radiation gamma background in the event of an accident or accident. With the conduct of military operations on the territory of Ukraine and in the Middle East, this danger should not be underestimated. Already in the 90s of the last centuries, systems for monitoring the radiation background were being built in Bulgaria for various ministries and departments. The report reviews some of these systems, analyzes their positive and negative sides, and makes recommendations for improving their functioning and optimizing the submitted data.